1999
DOI: 10.1111/j.1469-8749.1999.tb00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral style of young boys with fragile X syndrome

Abstract: To study the behavioral style or temperament of 45 boys, aged 47 to 88 months, with full-mutation fragile X syndrome (FXS), 102 parent ratings on the Behavioral Style Questionnaire were recorded. These ratings were analysed with a variety of statistical techniques. Considerable variability was evident in temperament profiles; consequently, a characteristic profile was not identified for FXS. Boys with FXS differed significantly from the reference sample on five of nine temperament dimensions. They were more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 53 publications
2
31
1
Order By: Relevance
“…This work has shown that children with autism (non-FXS) often do not respond to social stimuli in general (Dawson, Meltzoff, Osterling, Rinaldi, & Brown, 1998), and display less positive responses and more ''no responses'' than verbalmatched children with mental retardation (Jackson et al, 2003). In addition, our findings that social approach behaviors are associated with autistic behavior in boys with FXS are consistent with other reports (Hatton, Bailey, Hargett-Beck, Skinner, & Clark, 1999;Kaufmann et al, 2004). However, to our knowledge, this is the first study to report a relationship between modulation of social approach behaviors over time to autistic behavior in boys with FXS.…”
Section: Discussionsupporting
confidence: 93%
“…This work has shown that children with autism (non-FXS) often do not respond to social stimuli in general (Dawson, Meltzoff, Osterling, Rinaldi, & Brown, 1998), and display less positive responses and more ''no responses'' than verbalmatched children with mental retardation (Jackson et al, 2003). In addition, our findings that social approach behaviors are associated with autistic behavior in boys with FXS are consistent with other reports (Hatton, Bailey, Hargett-Beck, Skinner, & Clark, 1999;Kaufmann et al, 2004). However, to our knowledge, this is the first study to report a relationship between modulation of social approach behaviors over time to autistic behavior in boys with FXS.…”
Section: Discussionsupporting
confidence: 93%
“…First, it has been suggested that abnormalities in the frontal lobes of the brain result in a deficit in inhibiting high strength, salient, or previously activated responses, which results in repetitions of previously uttered forms and content or the intrusion of idiosyncratic material [Abbeduto and Hagerman, 1997]. In support of this hypothesis is the well-documented finding that individuals with FXS have impairments in attention and impulsivity that make it difficult for them to focus or direct their behavior for extended periods of time [Baumgardner and Reiss, 1994;Lachiewicz et al, 1994;Baumgardner et al, 1995;Cohen, 1995;Hagerman, 1996;Hatton et al, 1999;Miller et al, 1999]. Second, it has been suggested that impaired regulation of the autonomic nervous system, which results in hyperarousal, may exacerbate problems in inhibitory control, particularly in socially demanding or otherwise anxietyprovoking situations [Belser and Sudhalter, 1995;Cohen, 1995].…”
Section: Pragmaticsmentioning
confidence: 72%
“…Most young males with FraX display behavioral abnormalities that can be interpreted as atypical social interaction or autism spectrum behaviors [Hatton et al, 1999;Hagerman, 2002]; however, only a subset of boys with this genetic disorder fulfills FRAGILE X SYNDROME & AUTISM SPECTRUM DISORDER 9 A DSM-IV criteria for the diagnoses of autism or ASD [Bailey et al, 1998;. The importance of precisely delineating the behavioral profile of boys with FraX þ ASD is underscored by the fact that these children display other severe cognitive and behavioral abnormalities that have considerable medical and educational consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the prevalence of FraX þ Autism range between 16 and 47%, a reflection of differences in study design and methodology for assessing autistic features [Hagerman et al, 1986;Baumgardner et al, 1995;Bailey et al, 1998;Feinstein and Reiss, 1998;Rogers et al, 2001;Demark et al, 2003;Kaufmann et al, 2004]. An important factor influencing studies of autism in FraX is the fact that up to 90% of males with FraX display a variety of behavioral abnormalities that can be interpreted as atypical social interaction or autism spectrum behaviors such as perseveration, hand flapping, self-injury, avoidant eye contact, and social anxiety [Merenstein et al, 1996;Bailey et al, 1998;Hatton et al, 1999;Hagerman, 2002;Kaufmann et al, 2004]. We have recently reported that, when applying instruments specifically designed for evaluating autistic behavior such as the Autism Diagnostic Interview-Revised (ADI-R), most boys with FraX show autistic features .…”
Section: Introductionmentioning
confidence: 99%